MODEL/GAYA KEPEMIMPINAN RASULULLAH SAW - M. Abrar; Jamrizal; Minnah El Widdah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to find out the analogy of the characteristics of the leadership style of the Prophet Muhammad SAW and see leadership in the modern era in the field of education. The leadership of the Prophet Muhammad SAW provides an example for leaders to prioritize the interests of the people, teach and practice good morals, have traits such as honesty, trustworthiness, and concern for the people. In addition, he is also known as a democratic leader and always conducts deliberations in making decisions. His characteristics can be a guideline in the leadership of now era